UZUALNE PLURALIA TANTUM WE WSPÓŁCZESNEJ POLSZCZYŹNIE - Nowosad-Bakalarczyk, Marta (Studia Europaea Gnesnensia, 2017)
The article discusses nouns such as frytki, piegi, ścinki; being most often used in their plural form, makes them functionally resemble the pluralia tantum nouns (occurring exclusively in the plural). The author carries out a semantic analysis aimed at determining whether the meaning of a word (in this case) is a factor affecting its grammatical behaviour.